(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The current research aims to identify attitudes the kindergarten Teachers toward the role of kindergarten libraries in Developing the awareness of child of Kindergarten, also their extent availability the supports of library kindergarten from the Perspective of kindergarten Teachers, , and the different in the Attitudes to the following variables (scientific and educational qualification, experience, training courses, the authorities supervising), To achieve this research, questionnaire was built, consisted (44) items, which distributed for two axes, then applied to a sample of (174) kindergarten Teachers for the academic year 2015/2016, and the research used Descriptive method.. The results showed that the attitudes the kindergarten Teachers toward the role of kindergarten libraries in Developing the awareness of child of Kindergarten were a middle degree, also that the supports availability of library kindergarten were a middle degree, and officers showed no statistical significant different about the attitudes of the sample Research toward the role of kindergarten libraries in Developing the awareness of child of Kindergarten according to the variable experience, while statistical significant different according to the variable scientific and educational qualification in favor of masters, also different between the (Private, public) Kindergarten in favor of Private Kindergarten. The research provided some suggestions such as working to improvement the reality of Kindergarten libraries, in addition to conducting more research.